Structural design of compressible shape-memory foams for smart self-fixable electromagnetic shielding with reduced reflection. (January 2022) - Wang, Guoqing; Yi, Da; Jia, Xichen; Chen, Jiali; Shen, Bin; Zheng, Wenge
Abstract: To face the coexistence of the intended and unintended electromagnetic radiation in complex electromagnetic and harsh environment as well as minimize the secondary electromagnetic interference (EMI) pollution, the development of highly designable EMI shields for smart self-fixable EMI shielding with reduced reflection is of great importance. Herein, compressible shape-memory composite foams with strong structural designability have been fabricatd through a simple double dip-coating process, which could not only exhibit excellent shielding effectiveness (SE), but also achieve smart self-fixable SE adjustment under self-fixable compression originating from the ideal thermal/electrical-response shape-memory ability. More importantly, incorporating the concept of structural design, such as the construction of an asymmetric descending gradient structure or reasonable 3D patterns in the foams, could enhance the tunability of EM reflectivity effectively, which contributes to the reduction of EM reflection or even reverse the tendency of EM reflection to increase during the process of self-fixable compression-induced SE adjustment, thus minimizing the aggravated secondary EMI pollution significantly. The strategy and mechanism in this work highlights a significant plateau, on which smart self-fixable EMI shielding behavior with reduced reflection could be realized in highly designable shape-memory foam materials. Graphical abstract: Image 1 Highlights: Compressible shape-memory foams with strong structural designability are fabricatd through a double dip-coating process. Self-fixable compression originating from the shape-memory ability is proposed to achieve smart self-fixable SE adjustment. Incorporating structural design during compression-induced SE adjustment can enhance the tunability of EM reflection.